Polyamide composite membrane and preparation method thereof

By using a modified polyimide intermediate layer and a polyborosiloxane-based porous polymer substrate in the polyamide composite film, and adding inorganic nanoparticles to the intermediate layer, the problems of large differences in chemical properties, poor anti-pollution and susceptibility to substrates in the polyamide composite film are solved, and higher stability and anti-pollution properties are achieved.

CN119588183AActive Publication Date: 2025-03-11WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202510002504.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

During the use of existing polyamide composite films, there are problems such as large differences in the chemical properties of the intermediate layer material and the base material and the polyamide cortex, poor anti-pollution and easy damage to the polymer substrate.

Method used

A polyamide composite film using a polyborosiloxane-based porous polymer substrate, a modified polyimide intermediate layer and a polyamide separation layer is used to improve its weather resistance and compatibility with the substrate material by adding inorganic nanoparticles to the intermediate layer.

Benefits of technology

The interface bonding between the intermediate layer and the substrate and the polyamide cortex is enhanced, the overall stability and anti-pollution performance of the membrane are improved, and the risk of damage to the substrate is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225780600000081
    Figure BDA0005225780600000081
Patent Text Reader

Abstract

The invention relates to a polyamide composite membrane containing a middle layer and a preparation method of the polyamide composite membrane. The polyamide composite membrane comprises a polyborosiloxane-based porous polymer substrate, a modified polyimide middle layer and a polyamide separation layer, a modified polyimide intermediate layer is loaded on the surface of the porous polymer substrate, and a polyamide separation layer is loaded on the surface of the modified polyimide intermediate layer. The polyborosiloxane-based porous polymer substrate and the modified polyimide intermediate layer have better compatibility, interface defects can be reduced, the overall performance of the membrane can be improved, moreover, the polyborosiloxane-based porous polymer substrate also has a self-healing characteristic, and after the polyborosiloxane-based porous polymer substrate is damaged, the self-healing property of the polyborosiloxane-based porous polymer substrate is improved. Fractured connection can be repaired without external stimulation (such as light and heat), and self-repairing of the substrate is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane separation, in particular to a polyamide composite membrane and a preparation method thereof. Background Art

[0002] Polyamide composite membrane is a functional material that occupies an important position in membrane separation technology and is widely used in water treatment, food processing, pharmaceutical manufacturing and other fields. Its preparation process usually involves coating one or more layers of polymer film on a porous support material (substrate), in which the polyamide cortex acts as a separation layer and undertakes the main separation task. The polyamide cortex is favored for its good chemical stability, mechanical strength and separation performance. However, the preparation and performance optimization of polyamide composite membrane is a complex process involving the selection of multiple materials and the regulation of process parameters. Among them, the selection of the intermediate layer material plays a vital role in improving the bonding force between the polyamide cortex and the substrate, improving the anti-fouling performance and mechanical strength of the membrane, etc.

[0003] The existing polyamide composite membrane has the following disadvantages during use:

[0004] (1) The chemical properties of the middle layer material, base material and polyamide skin layer are very different:

[0005] In the preparation process of polyamide composite membranes, the selection of the intermediate layer material is often restricted by many factors, such as compatibility with the substrate material, bonding with the polyamide skin layer, and its own chemical stability. However, due to the significant differences in the chemical properties between the intermediate layer, the substrate, and the polyamide skin layer, this often leads to weak interfacial bonding between the membrane layers, which is prone to delamination or peeling, thus affecting the overall performance and stability of the membrane.

[0006] (2) Poor anti-pollution performance:

[0007] Polyamide composite membranes are easily contaminated by various pollutants during use, such as organic matter, inorganic salts, microorganisms, etc. These pollutants will adhere to the membrane surface or block the membrane pores, resulting in decreased membrane permeability and reduced separation efficiency. Although some polyamide composite membranes with good anti-pollution performance have been developed, there is still a problem of insufficient anti-pollution performance, especially when treating complex wastewater or high-concentration pollutants.

[0008] (3) The polymer substrate is easily damaged:

[0009] The substrate of polyamide composite membrane is usually made of polymer materials, such as polysulfone, polyethersulfone, etc. Although these polymer substrates have certain mechanical strength and chemical stability, they are still easily damaged by various factors during long-term use, such as chemical corrosion, physical wear, etc. Damage to the substrate will lead to a decrease in the overall performance of the membrane, and even cause the membrane to rupture or fail.

[0010] Therefore, we propose a polyamide composite membrane containing an intermediate layer and a preparation method thereof to solve the problems of large differences in chemical properties between the intermediate layer material and the base material and the polyamide skin layer, poor anti-pollution performance, and easy damage to the polymer base. Summary of the invention

[0011] The purpose of the present invention is to overcome the shortcomings of the prior art, meet actual needs, and provide a polyamide composite membrane containing an intermediate layer and a preparation method thereof, so as to solve the current problems in the polyamide composite membrane, such as the large difference in chemical properties between the intermediate layer material and the base material and the polyamide skin layer, poor anti-pollution performance, and easy damage to the polymer base.

[0012] In order to achieve the purpose of the present invention, the technical solution adopted by the present invention is:

[0013] A polyamide composite membrane containing an intermediate layer, comprising: a polyborosiloxane-based porous polymer substrate, a modified polyimide intermediate layer, and a polyamide separation layer;

[0014] The surface of the porous polymer substrate is loaded with a modified polyimide intermediate layer, and the surface of the modified polyimide intermediate layer is loaded with a polyamide separation layer.

[0015] In the present invention, the modified polyimide intermediate layer is prepared from a polyimide resin to which inorganic nanoparticles are added;

[0016] Preferably, the inorganic nanoparticles are selected from at least one of TiO2, ZrO2, Al2O3, SiO2, graphene, graphene oxide, and graphene quantum dots, and the size of the inorganic nanoparticles is preferably 1-100 nm, more preferably 10-60 nm.

[0017] Preferably, the modified polyimide intermediate layer is modified by doping with inorganic nanoparticles to improve its weather resistance, heat resistance, and chemical resistance to match the substrate material.

[0018] The present invention also provides a method for preparing the above-mentioned polyamide composite film containing an intermediate layer, comprising the following steps:

[0019] S1. Substrate preparation: dissolving polyborosiloxane in a solvent to form a polyborosiloxane solution, uniformly coating the polyborosiloxane solution on a carrier, then drying at a temperature of 60-80° C. for 2-4 hours, and then curing at a temperature of 100-150° C. for 8-12 hours to form a polyborosiloxane-based porous polymer substrate;

[0020] S2. Dispersion of inorganic nanoparticles: Mix the inorganic nanoparticles with a solvent, stir for about 1-2 hours, and control the rotation speed at 500-1000 rpm to uniformly disperse them to obtain a dispersion, and add the dispersion to a polyimide resin solution to form a polyimide resin solution containing inorganic nanoparticles;

[0021] S3, preparation of modified polyimide intermediate layer: uniformly coating a polyimide resin solution containing inorganic nanoparticles on a polyborosiloxane-based porous polymer substrate by coating, doctor blading, etc., and forming a nanoparticle-modified polyimide intermediate layer by appropriate drying and curing processes;

[0022] S4, preparation of polyamide separation layer: uniformly coating the polyamide separation layer material on the modified polyimide intermediate layer by a specific coating technology to obtain a coated composite membrane;

[0023] S5. Composite film curing: The coated composite film is cured at high temperature for about 0.5-12 hours, and the temperature is controlled at 60-180°C;

[0024] S6. Post-processing: Perform necessary post-processing on the cured composite film, such as cutting, trimming, cleaning, etc. If necessary, the composite film can also be subjected to performance testing and quality inspection.

[0025] Preferably, the solvents in S1 and S2 independently include at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), tetrahydrofuran, dichloromethane, water, methanol, ethanol, and isopropanol.

[0026] Preferably, the carrier in S1 may be an inorganic carrier or an organic polymer carrier, such as a porous alumina film or a polysulfone ultrafiltration membrane or a polyvinylidene fluoride microfiltration membrane.

[0027] Preferably, the molecular weight of the polyborosiloxane is 20000-100000 g / mol.

[0028] Preferably, the concentration of the polyborosiloxane solution is in the range of 5-50 wt %, preferably 10-30 wt %, more preferably 15-25 wt %.

[0029] Preferably, the coating thickness of the polyborosiloxane on the carrier is 5-100 μm.

[0030] Preferably, the concentration of the S2 dispersion is 0.5-10 wt %, preferably 1-5 wt %.

[0031] Preferably, the mass ratio of the inorganic nanoparticles to the polyimide resin is 2:100 to 30:100, preferably 10:100 to 20:100.

[0032] Preferably, the molecular weight of the polyimide resin is 50,000 to 200,000 g / mol.

[0033] Preferably, the concentration of the polyimide resin solution is 2-40 wt %, preferably 10-30 wt %.

[0034] Preferably, in S3, the modified polyimide intermediate layer is formed by drying at 50-75° C. for 1-3 h and then curing at 90-140° C. for 5-9 h, and the thickness of the modified polyimide intermediate layer is 20-180 μm, preferably 100-150 μm.

[0035] Preferably, the polyamide separation layer material in S4 is a polyamide solution;

[0036] Preferably, the polyamide molecular weight of the polyamide solution is 2000-500000 g / mol;

[0037] Preferably, the concentration of the polyamide solution is 2-75 wt%, preferably 20-35 wt%.

[0038] Preferably, the solvent of the polyamide solution includes at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), tetrahydrofuran, dichloromethane water, methanol, ethanol, and isopropanol.

[0039] Preferably, the specific coating technique in S4 is one of dipping, spraying or blade coating, and the coating thickness is 5-100 μm, preferably 10-40 μm, the drying temperature is 60-100° C., and the drying time is 10-60 min.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. The inorganic nanoparticles in the present invention can act as a bridge to enhance the interfacial bonding force between the intermediate layer and the substrate and the polyamide cortex through chemical bonding or physical adsorption. This helps to reduce the delamination or peeling phenomenon between the film layers, improve the overall stability and durability of the film, and the inorganic nanoparticles have excellent anti-pollution properties, such as hydrophilicity and antibacterial properties. Their addition can give the polyamide composite film better anti-pollution ability, reduce the attachment and accumulation of pollutants on the film surface, and solve the problem that the polyamide composite film is easily polluted by various pollutants (such as organic matter, inorganic salts, microorganisms, etc.) during use.

[0042] 2. The polyborosiloxane-based porous polymer substrate in the present invention has excellent chemical stability and can resist corrosion from a variety of chemical substances, thereby protecting the polyamide composite membrane from chemical corrosion. At the same time, the polyborosiloxane-based porous polymer substrate has better compatibility with the modified polyimide intermediate layer, which helps to reduce interface defects and improve the overall performance of the membrane. Moreover, the polyborosiloxane-based porous polymer substrate has self-healing properties. After being damaged, it can repair broken connections without external stimulation (such as light and heat), thereby realizing substrate self-repair.

[0043] 3. In the present invention, polyimide is modified by nanomaterials to improve its weather resistance, heat resistance, chemical resistance and other properties, so that it can better match the base material, and by matching it with a chemical structure and properties more similar to the polyamide cortex, it provides better compatibility and bonding strength. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with embodiments.

[0045] Main raw material sources:

[0046] Polyborosiloxane: Jiangxi Nan New Materials Co., Ltd., molecular weight: 50000 g / mol;

[0047] Polyimide resin: Qinyang Tianyi Chemical Co., Ltd., 705-292A;

[0048] Polyamide: Shanghai Huzheng Biotechnology Co., Ltd.

[0049] Embodiment 1

[0050] A method for preparing a polyamide composite film containing an intermediate layer comprises the following steps:

[0051] S1. Substrate preparation: polyborosiloxane was dissolved in DMF to form a polymer solution with a solid content of 20 wt%, and the obtained polymer solution was then uniformly coated on a porous alumina film with an average pore size of 0.23 μm and a thickness of 75 μm, followed by drying at 70° C. for 3 h and then curing at 130° C. for 10 h to form a polyborosiloxane-based porous polymer substrate;

[0052] S2, inorganic nanoparticle dispersion: SiO2 nanoparticles with an average particle size of 20 nm were uniformly dispersed in ethanol at a content of 0.5 wt%, and stirred at 750 rpm for 1.5 h. Then, they were slowly added to a DMF solution of polyimide resin with a solid content of 18%, wherein the mass ratio of SiO2 nanoparticles to polyimide resin was 10:100;

[0053] S3, preparation of modified polyimide intermediate layer: a polyimide resin solution containing inorganic nanoparticles is uniformly coated on a polyborosiloxane-based porous polymer substrate by spraying, and then dried at 75° C. for 2 h, and then cured at 120° C. for 8 h to form a modified polyimide intermediate layer with a thickness of 120 μm;

[0054] S4, preparation of polyamide separation layer: a 21 wt% NMP solution of polyamide is evenly coated on the modified polyimide intermediate layer by spraying, the coating thickness is 20 μm, the drying temperature is 75° C., and the drying time is 45 min, to ensure the uniformity and integrity of the separation layer;

[0055] S5. Composite film curing: The coated composite film is cured at high temperature for 10 hours at a temperature of 150°C.

[0056] S6. Post-processing: Use a laser cutting machine to cut the composite film into discs with a diameter of 75 mm, and carefully measure and mark to ensure accuracy; then, make the edges flat and smooth by removing burrs and trimming the shape; finally, choose anhydrous ethanol to rinse the surface three times to ensure that there is no residue, and dry it naturally in a dry and ventilated environment for use.

[0057] Embodiment 2

[0058] A method for preparing a polyamide composite film containing an intermediate layer comprises the following steps:

[0059] S1. Substrate preparation: polyborosiloxane was dissolved in DMAc to form a polymer solution with a solid content of 25 wt%, and the obtained polymer solution was evenly coated on a polysulfone ultrafiltration membrane with a thickness of 100 μm, followed by drying at 70° C. for 3 h and then curing at 130° C. for 10 h to form a polyborosiloxane-based porous polymer substrate;

[0060] S2, dispersion of inorganic nanoparticles: Graphene nanoparticles with an average particle size of 53 nm were uniformly dispersed in ethanol at a content of 1.0 wt%, and stirred continuously at 750 rpm for 1.5 h. Then, the mixture was slowly added to a DMF solution of polyimide resin with a solid content of 20 wt%, wherein the mass ratio of graphene nanoparticles to polyimide resin was 18:100;

[0061] S3, preparation of modified polyimide intermediate layer: a polyimide resin solution containing inorganic nanoparticles is uniformly coated on a polyborosiloxane-based porous polymer substrate by spraying, and then dried at 50° C. for 1.5 h, and then cured at 120° C. for 6 h to form a modified polyimide intermediate layer with a thickness of 140 μm;

[0062] S4, preparation of polyamide separation layer: a DMSO solution of polyamide with a concentration of 26 wt% is evenly coated on the modified polyimide intermediate layer by spraying, with a coating thickness of 20 μm, a drying temperature of 75° C., and a drying time of 45 min to ensure the uniformity and integrity of the separation layer;

[0063] S5. Composite film curing: The coated composite film is cured at high temperature for 10 hours at a temperature of 150°C.

[0064] S6. Post-processing: Use a laser cutting machine to cut the composite film into discs with a diameter of 75 mm, and carefully measure and mark to ensure accuracy; then, make the edges flat and smooth by removing burrs and trimming the shape; finally, choose anhydrous ethanol to rinse the surface three times to ensure that there is no residue, and dry it naturally in a dry and ventilated environment for use.

[0065] Embodiment 3

[0066] A method for preparing a polyamide composite film containing an intermediate layer comprises the following steps:

[0067] S1. Substrate preparation: polyborosiloxane was dissolved in DMSO to form a polymer solution with a solid content of 15 wt%, and the obtained polymer solution was evenly coated on a polyvinylidene fluoride microfiltration membrane with a thickness of 15 μm, followed by drying at 70° C. for 3 h and then curing at 120° C. for 10 h to form a polyborosiloxane-based porous polymer substrate;

[0068] S2, inorganic nanoparticle dispersion: TiO2 nanoparticles with an average particle size of 40nm were uniformly dispersed in DMF at a content of 5wt%, and stirred continuously at 750 rpm for 1.5h. Then, they were slowly added to a DMF solution of polyimide resin with a solid content of 25%, wherein the mass ratio of TiO2 nanoparticles to polyimide resin was 25:100;

[0069] S3, preparation of modified polyimide intermediate layer: a polyimide resin solution containing inorganic nanoparticles is uniformly coated on a polyborosiloxane-based porous polymer substrate by spraying, and then dried at 60° C. for 2 h, and then cured at 120° C. for 7 h to form a modified polyimide intermediate layer with a thickness of 160 μm;

[0070] S4, preparation of polyamide separation layer: a DMF solution of polyamide with a concentration of 30 wt% is evenly coated on the modified polyimide intermediate layer by spraying, the coating thickness is 30 μm, the drying temperature is 78° C., and the drying time is 55 min, to ensure the uniformity and integrity of the separation layer;

[0071] S5. Composite film curing: The coated composite film is cured at high temperature for 10 hours at a temperature of 150°C.

[0072] S6. Post-processing: Use a laser cutting machine to cut the composite film into discs with a diameter of 75 mm, and carefully measure and mark to ensure accuracy; then, make the edges flat and smooth by removing burrs and trimming the shape; finally, choose anhydrous ethanol to rinse the surface three times to ensure that there is no residue, and dry it naturally in a dry and ventilated environment for use.

[0073] Comparative Example 1

[0074] A simplified preparation method of a polyamide composite membrane containing an intermediate layer (without adding inorganic nanoparticles), the specific steps are as follows:

[0075] S1. Substrate preparation: polyborosiloxane was dissolved in DMF to form a polymer solution with a solid content of 20%, and then the obtained polymer solution was uniformly coated on a porous alumina film with an average pore size of 0.23 μm and a thickness of 75 μm, followed by drying at 70° C. for 3 h and then curing at 130° C. for 10 h to form a polyborosiloxane-based porous polymer substrate;

[0076] S2, (omit the inorganic nanoparticle dispersion step);

[0077] S3, preparation of polyimide intermediate layer: directly and evenly coating a DMF solution of polyimide resin with a solid content of 18% on the polyborosiloxane-based porous polymer substrate by spraying, and then drying at 75° C. for 2 h, and then curing at 120° C. for 8 h to form a polyimide intermediate layer with a thickness of 120 μm;

[0078] S4, preparation of polyamide separation layer: the same as in Example 1;

[0079] S5, composite film curing: the same as in Example 1;

[0080] S6, post-processing: the same as in Example 1.

[0081] Performance Test:

[0082] 1. Physical performance test

[0083] Tensile strength and elongation at break: refer to the film tensile properties test method in GB / T 13022-1991, the test temperature is 25±2℃, the relative humidity is 40%-60%, the stretching speed is 5mm / min, the maximum tensile force at the breaking point is recorded as the tensile strength Rm, the elongation at break of the sample is the elongation at break e, and the test results are obtained.

[0084] 2. Chemical stability and compatibility test

[0085] Solvent resistance: The dried sample was immersed in DMF at 25°C for 24 hours, then taken out and the residue was thoroughly washed with pure water, dried at 100°C for 30 minutes, and the dry weight before and after immersion in DMF was accurately weighed, and the weight loss rate after immersion in DMF was calculated.

[0086] Acid and alkali resistance: Soak the dried sample in a hydrochloric acid solution with a pH of 2 at 25°C for 24 hours, then use pure water to thoroughly wash the residue, and then dry it at 100°C for 30 minutes. Accurately weigh the dry weight before and after acid immersion, and calculate the weight loss after immersion to characterize the acid resistance of the sample;

[0087] The dried sample was immersed in a sodium hydroxide solution with a pH of 12 at 25°C for 24 hours, and then the residue was thoroughly cleaned with pure water. It was then dried at 100°C for 30 minutes. The dry weight before and after alkali immersion was accurately weighed, and the weight loss after immersion was calculated to characterize the alkali resistance of the sample.

[0088] Chemical compatibility: Soak the dried sample in NMP at 60°C for 24 hours, then take it out and use pure water to thoroughly clean the residue, dry it at 100°C for 30 minutes, and observe whether there is any shedding or peeling between the layers of the membrane to determine its chemical compatibility.

[0089] 3. Separation performance test

[0090] Permeation flux and retention rate: The cross-flow membrane performance evaluation equipment was used to test the membrane flux and retention rate. The effective area of ​​the membrane was 28.26 cm 2 , the feed temperature is 25°C, and the test pressure is 10 bar (gauge pressure);

[0091] Permeate flux refers to the volume of permeate that passes through a unit membrane area per unit time at 10 bar, expressed in J, and the calculation formula is as follows:

[0092] J=V / (T×S)

[0093] Where J is the permeation flux of the membrane, in L / m2 h; V is the volume of the exudate during the test time L; T is the sampling time, in h; S is the effective area of ​​the membrane, in m 2 ;

[0094] The conductivity of the exudate and the original solution was measured using a conductivity meter, and the interception rate was calculated as follows:

[0095] R=(1-Cp / Cf)×100%

[0096] Where R refers to the retention rate, %; Cp refers to the permeate concentration, in ppm; Cf refers to the feed concentration, in ppm;

[0097] The feed liquid is configured as 2000ppm MgSO4 solution. Before the formal test, it is necessary to pre-pressurize for 0.5h to stabilize the membrane performance, and then conduct the separation performance test.

[0098] 4. Anti-pollution performance test

[0099] Continuous filtration test: The membrane's anti-fouling performance is characterized by measuring the flux change after continuous filtration for 24 hours at a feed temperature of 25°C and a test pressure of 10 bar (gauge pressure). The water flux J after continuous filtration for 24 hours is calculated. w and initial water flux J w,0 The ratio of (1-J w / J w,0 ) is used as the flux attenuation rate after pollution, and then the degree of water flux attenuation is determined to evaluate the membrane's anti-pollution performance.

[0100] Cleaning recovery: After the membrane anti-fouling performance test, use pure water as the feed liquid to clean the membrane surface. The feed temperature is 25°C, the operating pressure is 10 bar, and the cleaning is continuous for 30 minutes. Calculate the water flux J after cleaning w,1 and initial water flux J w,0 The ratio J w,1 / J w,0 The flux recovery rate after cleaning is used to determine the recovery after contamination and to evaluate the recovery ability of the membrane after contamination.

[0101] 5. Self-healing test

[0102] A 5-10 μm scratch was manually made on the film surface with a blade. The film was placed in an 80°C temperature atmosphere for 30 minutes, and the scratch self-healing was observed under an optical microscope. By observing the scratch width repair, the self-healing performance of the material can be clearly observed.

[0103] The test results of the embodiments and comparative examples are as follows:

[0104] Table 1 Diaphragm performance test data

[0105]

[0106] The embodiments of the present invention disclose preferred embodiments, but are not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.

Claims

1. A polyamide composite membrane, characterized in that: include: A polyborosiloxane-based porous polymer substrate, a modified polyimide intermediate layer, and a polyamide separation layer; The surface of the porous polymer substrate is loaded with a modified polyimide intermediate layer, and the surface of the modified polyimide intermediate layer is loaded with a polyamide separation layer; The modified polyimide intermediate layer is prepared from a polyimide resin added with inorganic nanoparticles.

2. The polyamide composite membrane according to claim 1, characterized in that The inorganic nanoparticles are selected from at least one of TiO2, ZrO2, Al2O3, SiO2, graphene, graphene oxide, and graphene quantum dots. Preferably, the size of the inorganic nanoparticles is 1-100 nm.

3. A method for preparing a polyamide composite membrane according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Substrate preparation: evenly coating the polyborosiloxane solution on the carrier, drying, and curing to form a polyborosiloxane-based porous polymer substrate; S2, dispersing inorganic nanoparticles: mixing the inorganic nanoparticles with a solvent to obtain a dispersion, and mixing the dispersion with a polyimide resin solution to form a polyimide resin solution containing the inorganic nanoparticles; S3, preparation of modified polyimide intermediate layer: uniformly coating a polyimide resin solution containing inorganic nanoparticles on a polyborosiloxane-based porous polymer substrate, drying, and curing to form a modified polyimide intermediate layer; S4, preparation of polyamide separation layer: uniformly coating the polyamide separation layer material on the modified polyimide intermediate layer to obtain a coated composite membrane; S5, composite film curing: curing the coated composite film; S6. Post-processing: performing post-processing on the cured composite film.

4. The preparation method according to claim 3, characterized in that: The solvents in S1 and S2 independently include at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), tetrahydrofuran, dichloromethane, water, methanol, ethanol, and isopropanol.

5. The preparation method according to claim 3 or 4, characterized in that: S1 The carrier is selected from an inorganic carrier or an organic polymer carrier, such as a porous alumina film or a polysulfone ultrafiltration membrane, or a polyvinylidene fluoride microfiltration membrane; Preferably, the molecular weight of the polyborosiloxane is 20000-100000 g / mol; Preferably, the concentration of the polyborosiloxane solution is 5-50wt%; Preferably, the coating thickness of the polyborosiloxane on the carrier is 5-100 μm; Preferably, S1 is dried at a temperature of 60-80°C for 2-4 hours and cured at a temperature of 100-150°C for 8-12 hours.

6. The preparation method according to claim 3 or 4, characterized in that: The concentration of S2 dispersion is 0.5-10wt%; Preferably, the mass ratio of the inorganic nanoparticles to the polyimide resin is 2:100 to 30:100, preferably 10:100 to 20:100; Preferably, the molecular weight of the polyimide resin is 50,000 to 200,000 g / mol; Preferably, the concentration of the polyimide resin solution is 2-40 wt %.

7. The preparation method according to claim 3, characterized in that: In S3, drying is performed at 50-75°C for 1-3 hours, and curing is performed at 90-140°C for 5-9 hours; preferably, the thickness of the modified polyimide intermediate layer is 20-180 μm, preferably 100-150 μm.

8. The preparation method according to claim 3, characterized in that: The polyamide separation layer material in S4 is a polyamide solution; Preferably, the concentration of the polyamide solution is 2-75wt%; Preferably, the solvent of the polyamide solution includes at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), tetrahydrofuran, dichloromethane water, methanol, ethanol, and isopropanol; Preferably, the coating thickness is 5-100 μm, preferably 10-40 μm, the drying temperature is 60-100° C., and the drying time is 10-60 min.

9. The preparation method according to claim 3, characterized in that: In S5, the curing is carried out at 60-180°C for 0.5-12h.

10. The preparation method according to claim 3, characterized in that: In S6, the post-processing is selected from cutting, trimming, and cleaning.

Citation Information

Patent Citations

  • Multi-layer composite biomass water treatment membrane

    CN110180407A

  • Quick self-repairing polyborosiloxane film and preparation method thereof

    CN116082678A

  • Organic solvent-resistant nanofiltration membrane containing active intermediate layer and active nanoparticles and preparation method thereof

    CN117160244A

  • Polyamide composite membrane as well as preparation method and application thereof

    CN117358069A

  • Method for manufacturing water-treatment membrane, water-treatment membrane manufactured by thereof, and water treatment module comprising membrane

    KR1020170091970A

Cited By

  • Seawater desalination reverse osmosis membrane based on graphene-polyamide material and preparation method thereof

    CN121648751A